On a new species of the genus adelobothrium, shipley (1900) from the intestine of marine fish carcharias acutus - Mote, Ashok (International Multidisciplinary Research Journal, 2011)
The genus Adelobothrium, was eastablished by Shipley, in 1900 [1], as Aetiobatidis from Aediobaties narinari from Loyalty, Island. Later on no species is added to this genus. Ten mature specimens of the cestode parasites were collected from the spiral valve Carcharis acutus. The present species differ from all other known species of the genus, scolex large, blunt, round antriorly, posteror region membranous, oval in shape, provided with four accessory suckers, neck present, matures gements crapedote, longer broad, testes, rounded, cirrus pouch large, oval sub â€“ marginal, extend beyond the middle of the segments, ovary bilobed, irregular margin, numerous acini vitellaria follicular.Â